It's not your money : how to live fully from divine abundance - Silver, Tosha (Hay House Inc., 2019)
"From the author of the acclaimed Outrageous Openness, a witty and spirited guide to radically releasing the burden of financial fears It's natural to crave prosperity. Some seek to manifest it in myriad ways--using anything from vision boards to writing a pretend check for a million dollars from the Bank of Divinity. Yet whatever comes, or doesn't, the mind always seems to want more. But what if there was a whole other way? Instead of grasping and chasing, what if we offered everything--our money (or lack of it), our triumphs, our problems, our desires--fully back to Love? What if this offering itself was actually the secret to abundance? Tosha Silver, internationally beloved spiritual guide, has created a practical and powerful financial book unlike any other. Leading you through a deeply transformative eight-week process, she shares the mental, emotional, and spiritual steps that anyone can take to learn to fully receive and prosper. Her step-by-step guidance is filled with prayers, meditations, and stories to help you find and heal the source of these fears and unworthiness. As you come to know you are part of something larger--something that you serve and that longs to serve you--you begin to feel a new sense of freedom and abundance"--